Metal(loid) accumulation in aquatic plants of a mining area: Potential for water quality biomonitoring and biogeochemical prospecting. (March 2018) - Favas, Paulo J.C.; Pratas, João; Rodrigues, Nelson; D'Souza, Rohan; Varun, Mayank; Paul, Manoj S.
Abstract: Aquatic bryophytes can accumulate extremely high levels of chemical elements because of their unique morphology and physiology which is markedly different from vascular plants. Four aquatic mosses— Fontinalis squamosa, Brachythecium rivulare, Platyhypnidium riparioides, Thamnobryum alopecurum —and a freshwater red alga Lemanea fluviatilis along with water samples from the streams of Góis mine region in Central Portugal were analyzed for 46 elements. Despite being below detection levels in the water samples, the elements Zr, V, Cr, Mo, Ru, Os, Rh, Ir, Pt, Ag, Ge and Bi were obtained in the plant samples. The moss T. alopecurum had the highest mean concentrations of 19 elements followed by B. rivulare (15 elements). Maximum accumulation of Rb, Ta and Au, however, was seen in the alga L. fluviatilis. Bioconcentration factors > 10 6 were obtained for a few metals. The investigation confirms that aquatic bryophytes can be suitable for water quality biomonitoring and biogeochemical prospecting in fresh water bodies owing to their high accumulative capacity of multi-elements from their aquatic ambient. Graphical abstract: Highlights: This work focused on multi-element accumulation by aquatic plants in field conditions. A set of plant species was found with the ability to accumulate several elements. The studied aquatic bryophytes can be suitable for water quality biomonitoring. Thamnobryum alopecurum and Brachythecium rivulare reveal high accumulative capacity. The alga Lemanea fluviatilis hold promise in the context of some metals (Rb, Ta, Au).